Willingness to protect bird species depends on individual respondents' demographic and species traits - Christoph Randler; Sophia Koch (Conservation Science and Practice)
Abstract Willingness to donate and to protect (WTP) is an important part of worldwide nature conservation, and animals can be used as flagships for establishing conservation measures and collecting donations. We here focus on 141 German bird species to address factors that impact WTP by using a survey on the individual respondent level. Further, another analysis assessed traits on the species level. A total of 1003 respondents participated in the survey. Results of an analysis of covariance suggest that, at the level of the individual, subjective cuteness rating, coloration, species knowledge, and age positively influenced WTP. On the species trait level based on the 141 species, cuteness, coloration, and internet salience were positively related to WTP, and presence at feeders, eBird entries, and global abundance were negatively related to WTP. This is one of the first studies based on a large number of bird species from Europe and it can inform regional nongovernmental organizations for selecting charismatic species for conservation communications. Moreover, this study consequently addresses cuteness in birds as an important factor.